Drivers of roe deer use in fragmented forest landscapes; implications for current and future management in the context of policy driven forest expansion - Saudamini Venkatesan; Benjamin M. Marshall; Mark S. Greener; Anna Kinghorn; Isla Sligo-Young; Richard Hassall; Robin Gill; Ben McKeown; Jeanette Hall; Roman Biek; Lucy Gilbert; Thomas A. Morrison; et al. (Forest Ecology and Management, 2026)

Abundance-based distribution modelling reveals climate-driven loss of functionally important kelp forest habitat - Patrick Eskuche-Keith; Heather E. Sugden; Michael T. Burrows; Pippa J. Moore; Clare Fitzsimmons; Dan A. Smale; Benjamin Hall; Fabrice Stephenson (Journal of Environmental Management, 2026)

Forest restoration thinning and burning treatments create habitat mosaics and facilitate succession of grasshopper and cricket communities (Orthoptera) - Robert R. Parmenter; Tyler J. Obermeit; Benjamin P. Stout; Sarah M. Hall; Orrin B. Myers; David C. Lightfoot (Forest Ecology and Management, 2026)

Statins and postmenopausal breast cancer risk; results from the KARMA cohort - Marie Klintman; Ann H. Rosendahl; Benjamin R. Johannesen; Deirdre Cronin-Fenton; Mikael Eriksson; Kamila Czene; Per Hall; Signe Borgquist (Cancer Causes & Control, 2026)
Purpose To study the incidence and subtype of breast cancer in relation to incident and prevalent statin use in a contemporary Swedish prospective cohort, The Karolinska Mammography Project for Risk Prediction of Breast Cancer, KARMA. Methods A total of 35,315 postmenopausal women attending mammography and included in the KARMA cohort (Jan 2011–March 2013) with data on statin use and potential confounders were studied. During eight years of follow-up, 785 incident invasive breast cancer cases were identified. Results A total of 16% of women were prevalent statin users (prior to study inclusion) and 9% were incident statin users (following study inclusion). In multivariable Cox regression analyses, there was no significant association between incident or prevalent statin use and risk of incident breast cancer (HR adj 1.24, 95% CI 0.89–1.72, and HR adj 0.90, 95% CI 0.73–1.11, respectively). Similarly, no significant association was found for incident or prevalent statin use and subtype-specific risk of breast cancer. Conclusion This prospective population-based study performed in a modern screening population with a substantial number of statin users, concurs with previous publications showing no evidence of an association between statin use and risk of postmenopausal breast cancer.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Co-creating water knowledge: a community perspective - Giulio Castelli; Ben C. Howard; Tanveer M. Adyel; Amir AghaKouchak; Afnan Agramont; Hafzullah Aksoy; Rossella Alba; Pedro H.L. Alencar; Amobichukwu C. Amanambu; Hasnat Aslam; Luna Bharati; Liduin Bos-Burgering; et al. (Hydrological Sciences Journal, 2025)

Correction: Identifying high risk seafloor areas to bottom trawling in Aotearoa New Zealand to support marine Spatial management - Benjamin Hall; Matthew Bennion; Orlando Lam-Gordillo; Clare Fitzsimmons; Fabrice Stephenson (Biodiversity and Conservation, 2025)

The industrial decarbonization paradigm: Carbon lock-in or path renewal in the United Kingdom? - Kyle S. Herman; Jeremy K. Hall; Benjamin K. Sovacool; Marfuga Iskandarova (Ecological Economics, 2025)

Identifying high risk seafloor areas to bottom trawling in Aotearoa New Zealand to support marine spatial management - Benjamin Hall; Matthew Bennion; Orlando Lam-Gordillo; Clare Fitzsimmons; Fabrice Stephenson (Biodiversity and Conservation, 2025)
Seafloor species play important ecological roles within marine ecosystems, yet many are vulnerable to the impacts of bottom fishing. Despite the known vulnerability of many seafloor taxa, destructive bottom fishing remains prevalent in many parts of the world given demand for wild-caught seafood. Species Distribution Models (SDMs) are increasingly used to estimate the distribution of vulnerable taxa and estimate possible risk of interactions with fishing gears, but most approaches have used a limited number of taxa. In this study, spatial predictions of species distributions for 207 seafloor invertebrate taxa in New Zealand waters were combined with a comprehensive database of functional traits related to bottom trawling to predict areas of high vulnerability. In addition, this study combined functional redundancy and vulnerability scores to identify ‘high combined risk’ areas that covered 182,087 km 2 (9.5%) of the study area. The interactions of these areas with current Marine Management Areas (MMAs) and highly fished zones revealed that current MMAs protect 50% of the ‘high combined risk’ areas (91,000 km 2 ), and less than 1% is within fished areas. This leaves a predicted 90,937 km 2 (49%) outside current protection, some are close to current MMAs and are potentially of high priority for future marine spatial management. Identifying areas most vulnerable to bottom trawling showcases interactions within previously fished areas (areas that have been fished in the past and could potentially be fished again), as well as highlighting areas for management action. Using different sets of functional traits as a combined approach could also be used to assess other anthropogenic impacts, improving ecosystem-based spatial management by ensuring protection of functions at globally significant scales.

Drivers of Regional Variability in Producer and Consumer Stable Isotope Values (δ13C and δ15N) Within Turtle Grass-Dominated Meadows Across the Northern Gulf of Mexico - Christian Todd Hayes; Scott B. Alford; Benjamin A. Belgrad; Kelly M. Correia; M. Zachary Darnell; Kevin S. Dillon; Bradley T. Furman; Margaret O. Hall; Charles W. Martin; Ashley M. McDonald; Delbert L. Smee; Samantha M. Smith; et al. (Estuaries and Coasts, 2025)

Utilization of Fish Meal and Fish Oil from Smoked Salmon By-Products in Juvenile Striped Bass (Morone saxatilis) Feeds: Growth Performance, Nutritional Composition, and Shelf-Life Assessment of Upcycled Ingredients - Connor Neagle; Michael O. Frinsko; Ryan Kelly; Steven G. Hall; Benjamin J. Reading; Alexander Chouljenko; Greg Bolton; Michael Joseph (Fishes, 2025)
Fish meal (FM) and fish oil (FO) are vital components commonly used in feed formulations. However, their supply, which generally comes from capture fisheries, is being exhausted, necessitating the exploration of sustainable alternatives. In a two-part study, the first part evaluated the FM and FO derived from smoked salmon by-product (SSBP) over a 12-week accelerated shelf-life test, comparing their lipid oxidation, amino acid, and fatty acid profiles to those of commercial whitefish meal and oil. In the second part, the SSBP FM and FO were then included in three experimental feeds at 25%, 50%, and 100% inclusion levels. These feeds were tested on juvenile striped bass (Morone saxatilis) cultured in a recirculating aquaculture system (RAS). The results indicated that the quality of SSBP FM and FO was lower than the commercial product (less amino acids (23.98% vs. 60.30%) and omega-3 fatty acids (9.46% vs. 26.6%), respectively). SSBP FO exhibited high initial peroxide value (21.00 ± 0.00 meq/kg oil), with gradually increasing total oxidation value and p-Anisidine value during storage. Regarding the feeding trial, all fish showed signs of Mycobacterium marinum infection after one month. While there was no significant difference in feed palatability (p > 0.8559), the feed conversion ratio was less efficient for the 100% SSBP feed (1.44 ± 0.14) compared to commercial feed (1.36 ± 0.13), but these differences were not statistically significant. This study suggests that SSBP FM and FO can be used as supplements at lower levels (25% and 50%) without negatively affecting growth, feed efficiency, or survival. Our findings may be useful for enabling beneficial collaborations between smoked salmon processors, feed manufacturers, and striped bass farmers, therefore contributing to sustainability in aquaculture practices.

A Future of Self-Directed Patient Internet Research: Large Language Model-Based Tools Versus Standard Search Engines - Arya Rao; Andrew Mu; Elizabeth Enichen; Dhruva Gupta; Nathan Hall; Erica Koranteng; William Marks; Michael J. Senter-Zapata; David C. Whitehead; Benjamin A. White; Sanjay Saini; Adam B. Landman; et al. (Annals of Biomedical Engineering, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Restorative function of offshore longline mussel farms with ecological benefits for commercial crustacean species - Thomas Stamp; Simon J. Pittman; Luke A. Holmes; Adam Rees; Benjamin J. Ciotti; Harry Thatcher; Peter Davies; Alice Hall; Georgia Wells; Anna Olczak; Emma V. Sheehan (Science of The Total Environment, 2024)

Water temperature affects somatic growth, body condition and oxygen and carbon otolith isotopes of stout whiting (Sillago robusta) - Melissa Tan; Karina C. Hall; Sebastian Litchfield; Curtis Champion; Matheus Carvalho de Carvalho; Benjamin Mos; Symon Dworjanyn; Brendan P. Kelaher (Science of The Total Environment, 2024)

“Oh Yes! Net-Zero”: Sociotechnical capabilities and regional innovation systems for British industrial decarbonization - Benjamin K. Sovacool; Kyle S. Herman; Marfuga Iskandarova; Jeremy K. Hall (Environmental Innovation and Societal Transitions, 2024)

Hurricane Effects on Seagrass and Associated Nekton Communities in the Northern Gulf of Mexico - Kelly M. Correia; Scott B. Alford; Benjamin A. Belgrad; Kelly M. Darnell; M. Zachary Darnell; Bradley T. Furman; Margaret O. Hall; Christian T. Hayes; Charles W. Martin; Ashley McDonald; Delbert L. Smee (Estuaries and Coasts, 2024)

Hazard assessment and monitoring of Ecuadorian volcanoes: challenges and progresses during four decades since IG-EPN foundation - Silvana Hidalgo; Benjamin Bernard; Patricia Mothes; Cristina Ramos; Jorge Aguilar; Daniel Andrade; Pablo Samaniego; Hugo Yepes; Minard Hall; Alexandra Alvarado; Mónica Segovia; Mario Ruiz; et al. (Bulletin of Volcanology, 2023)

Persistent organic pollutants and trace elements detected in New Zealand fur seals (long-nosed fur seal; Arctocephalus forsteri) from New South Wales, Australia, between 1998 and 2019 - Jane Hall; Susan Bengtson Nash; Anil Gautam; Hannah Bender; Benjamin J. Pitcher; Hamish McCallum; Christopher Doyle (Science of The Total Environment, 2023)

Monitoring medication and illicit drug consumption in a prison by wastewater-based epidemiology: Impact of COVID-19 restrictions - Zhe Wang; Jochen F. Mueller; Jake W. O'Brien; Jack Thompson; Benjamin J. Tscharke; Rory Verhagen; Qiuda Zheng; Jeremy Prichard; Wayne Hall; Keith Humphreys; Kevin V. Thomas; Phong K. Thai (Water Research, 2023)

Aspirin and Subarachnoid Haemorrhage in the UK Biobank - Frederick Ewbank; Jacqueline Birks; Benjamin Gaastra; Samuel Hall; Ian Galea; Diederik Bulters (Translational Stroke Research, 2023)

Assay measurement of gaseous UF6 using femtosecond laser-induced breakdown spectroscopy in the 424.4 nm spectral region - Benjamin S. Jordan; Jason D. Readle; Jeffrey R. Cooper; Matthew Cook; Jason P. Hayward; J. Daniel Hartman; Dean Forrest; Howard L. Hall (Annals of Nuclear Energy, 2023)

Stability of patch‐turnover relationships under equilibrium and nonequilibrium metapopulation dynamics driven by biogeography - Steven R. Beissinger; Sean M. Peterson; Laurie A. Hall; Nathan Van Schmidt; Jerry Tecklin; Benjamin B. Risk; Orien M. Richmond; Tony J. Kovach; A. Marm Kilpatrick (Ecology Letters, 2022)
Two controversial tenets of metapopulation biology are whether patch quality and the surrounding matrix are more important to turnover (colonisation and extinction) than biogeography (patch area and isolation) and whether factors governing turnover during equilibrium also dominate nonequilibrium dynamics. We tested both tenets using 18 years of surveys for two secretive wetland birds, black and Virginia rails, during (1) a period of equilibrium with stable occupancy and (2) after drought and arrival of West Nile Virus (WNV), which resulted in WNV infections in rails, increased extinction and decreased colonisation probabilities modified by WNV, nonequilibrium dynamics for both species and occupancy decline for black rails. Area (primarily) and isolation (secondarily) drove turnover during both stable and unstable metapopulation dynamics, greatly exceeding the effects of patch quality and matrix conditions. Moreover, slopes between turnover and patch characteristics changed little between equilibrium and nonequilibrium, confirming the overriding influences of biogeographic factors on turnover.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Environmental Drivers of Seagrass-Associated Nekton Abundance Across the Northern Gulf of Mexico - Benjamin A. Belgrad; Kelly M. Correia; Kelly M. Darnell; M. Zachary Darnell; Christian T. Hayes; Margaret O. Hall; Bradley T. Furman; Charles W. Martin; Delbert L. Smee (Estuaries and Coasts, 2021)

Response to “Connectivity and pore accessibility in models of soil carbon cycling” - Bonnie G. Waring; Benjamin N. Sulman; Sasha Reed; A. Peyton Smith; Colin Averill; Courtney A. Creamer; Daniela F. Cusack; Steven J. Hall; Julie D. Jastrow; Andrea Jilling; Kenneth M. Kemner; Markus Kleber; et al. (Global Change Biology, 2021)
Here we respond to Baveye and colleagues' recent critique of our PROMISE model, describing how this new framework significantly advances our understanding of soil spatial heterogeneity and its influence on organic matter transformations.

Influence of neighbourhoods on the extent and compactness of tropical tree crowns and root systems - Christopher Madsen; Matthias Kunz; Goddert von Oheimb; Jefferson Hall; Katherine Sinacore; Benjamin L. Turner; Catherine Potvin (Trees, 2021)

Differential household vulnerability to climatic and non-climatic stressors in semi-arid areas of Mali, West Africa - Alcade C. Segnon; Edmond Totin; Robert B. Zougmoré; Jourdain C. Lokossou; Mary Thompson-Hall; Benjamin O. Ofori; Enoch G. Achigan-Dako; Christopher Gordon (Climate and Development, 2021)

Response to ‘Stochastic and deterministic interpretation of pool models’ - Bonnie G. Waring; Benjamin N. Sulman; Sasha Reed; A. Peyton Smith; Colin Averill; Courtney A. Creamer; Daniela F. Cusack; Steven J. Hall; Julie D. Jastrow; Andrea Jilling; Kenneth M. Kemner; Markus Kleber; et al. (Global Change Biology, 2021)

Tree density effects on soil, herbage mass and nutritive value of understory Megathyrsus maximus in a seasonally dry tropical silvopasture in Panama - Ryan Dibala; Shibu Jose; Michael Gold; Jefferson S. Hall; Robert Kallenbach; Benjamin Knapp (Agroforestry Systems, 2021)

From pools to flow: The PROMISE framework for new insights on soil carbon cycling in a changing world - Bonnie G. Waring; Benjamin N. Sulman; Sasha Reed; A. Peyton Smith; Colin Averill; Courtney A. Creamer; Daniela F. Cusack; Steven J. Hall; Julie D. Jastrow; Andrea Jilling; Kenneth M. Kemner; Markus Kleber; et al. (Global Change Biology, 2020)
Soils represent the largest terrestrial reservoir of organic carbon, and the balance between soil organic carbon (SOC) formation and loss will drive powerful carbon‐climate feedbacks over the coming century. To date, efforts to predict SOC dynamics have rested on pool‐based models, which assume classes of SOC with internally homogenous physicochemical properties. However, emerging evidence suggests that soil carbon turnover is not dominantly controlled by the chemistry of carbon inputs, but rather by restrictions on microbial access to organic matter in the spatially heterogeneous soil environment. The dynamic processes that control the physicochemical protection of carbon translate poorly to pool‐based SOC models; as a result, we are challenged to mechanistically predict how environmental change will impact movement of carbon between soils and the atmosphere. Here, we propose a novel conceptual framework to explore controls on belowground carbon cycling: P robabilistic R epresentation of O rganic M atter I nteractions within the S oil E nvironment (PROMISE). In contrast to traditional model frameworks, PROMISE does not attempt to define carbon pools united by common thermodynamic or functional attributes. Rather, the PROMISE concept considers how SOC cycling rates are governed by the stochastic processes that influence the proximity between microbial decomposers and organic matter, with emphasis on their physical location in the soil matrix. We illustrate the applications of this framework with a new biogeochemical simulation model that traces the fate of individual carbon atoms as they interact with their environment, undergoing biochemical transformations and moving through the soil pore space. We also discuss how the PROMISE framework reshapes dialogue around issues related to SOC management in a changing world. We intend the PROMISE framework to spur the development of new hypotheses, analytical tools, and model structures across disciplines that will illuminate mechanistic controls on the flow of carbon between plant, soil, and atmospheric pools.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Automated lifespan determination across Caenorhabditis strains and species reveals assay-specific effects of chemical interventions - Stephen A. Banse; Mark Lucanic; Christine A. Sedore; Anna L. Coleman-Hulbert; W. Todd Plummer; Esteban Chen; Jason L. Kish; David Hall; Brian Onken; Michael P. Presley; E. Grace Jones; Benjamin W. Blue; et al. (GeroScience, 2019)
The goal of the Caenorhabditis Intervention Testing Program is to identify robust and reproducible pro-longevity interventions that are efficacious across genetically diverse cohorts in the Caenorhabditis genus. The project design features multiple experimental replicates collected by three different laboratories. Our initial effort employed fully manual survival assays. With an interest in increasing throughput, we explored automation with flatbed scanner-based Automated Lifespan Machines (ALMs). We used ALMs to measure survivorship of 22 Caenorhabditis strains spanning three species. Additionally, we tested five chemicals that we previously found extended lifespan in manual assays. Overall, we found similar sources of variation among trials for the ALM and our previous manual assays, verifying reproducibility of outcome. Survival assessment was generally consistent between the manual and the ALM assays, although we did observe radically contrasting results for certain compound interventions. We found that particular lifespan outcome differences could be attributed to protocol elements such as enhanced light exposure of specific compounds in the ALM, underscoring that differences in technical details can influence outcomes and therefore interpretation. Overall, we demonstrate that the ALMs effectively reproduce a large, conventionally scored dataset from a diverse test set, independently validating ALMs as a robust and reproducible approach toward aging-intervention screening.

Cost-effectiveness of breast cancer screening in the National Breast and Cervical Cancer Early Detection Program - Sun Hee Rim; Benjamin T. Allaire; Donatus U. Ekwueme; Jacqueline W. Miller; Sujha Subramanian; Ingrid J. Hall; Thomas J. Hoerger (Cancer Causes & Control, 2019)

Phosphatase activity and nitrogen fixation reflect species differences, not nutrient trading or nutrient balance, across tropical rainforest trees - Sarah A. Batterman; Jefferson S. Hall; Benjamin L. Turner; Lars O. Hedin; J. Kimiko LaHaela Walter; Pete Sheldon; Michiel van Breugel (Ecology Letters, 2018)
A fundamental biogeochemical paradox is that nitrogen‐rich tropical forests contain abundant nitrogen‐fixing trees, which support a globally significant tropical carbon sink. One explanation for this pattern holds that nitrogen‐fixing trees can overcome phosphorus limitation in tropical forests by synthesizing phosphatase enzymes to acquire soil organic phosphorus, but empirical evidence remains scarce. We evaluated whether nitrogen fixation and phosphatase activity are linked across 97 trees from seven species, and tested two hypotheses for explaining investment in nutrient strategies: trading nitrogen‐for‐phosphorus or balancing nutrient demand. Both strategies varied across species but were not explained by nitrogen‐for‐phosphorus trading or nutrient balance. This indicates that (1) studies of these nutrient strategies require broad sampling within and across species, (2) factors other than nutrient trading must be invoked to resolve the paradox of tropical nitrogen fixation, and (3) nitrogen‐fixing trees cannot provide a positive nitrogen‐phosphorus‐carbon feedback to alleviate nutrient limitation of the tropical carbon sink.

Using unsupervised learning techniques to assess interactions among complex traits in soybeans - Alencar Xavier; Benjamin Hall; Shaun Casteel; William Muir; Katy Martin Rainey (Euphytica, 2017)

A global database of nitrogen and phosphorus excretion rates of aquatic animals - Michael J. Vanni; Peter B. McIntyre; Dennis Allen; Diane L. Arnott; Jonathan P. Benstead; David J. Berg; Åge Brabrand; Sébastien Brosse; Paul A. Bukaveckas; Adriano Caliman; Krista A. Capps; Luciana S. Carneiro; et al. (Ecology, 2017)
Animals can be important in modulating ecosystem‐level nutrient cycling, although their importance varies greatly among species and ecosystems. Nutrient cycling rates of individual animals represent valuable data for testing the predictions of important frameworks such as the Metabolic Theory of Ecology ( MTE ) and ecological stoichiometry ( ES ). They also represent an important set of functional traits that may reflect both environmental and phylogenetic influences. Over the past two decades, studies of animal‐mediated nutrient cycling have increased dramatically, especially in aquatic ecosystems. Here we present a global compilation of aquatic animal nutrient excretion rates. The dataset includes 10,534 observations from freshwater and marine animals of N and/or P excretion rates. These observations represent 491 species, including most aquatic phyla. Coverage varies greatly among phyla and other taxonomic levels. The dataset includes information on animal body size, ambient temperature, taxonomic affiliations, and animal body N:P. This data set was used to test predictions of MTE and ES , as described in Vanni and McIntyre (2016; Ecology DOI : 10.1002/ecy.1582 ).

Liana effects on biomass dynamics strengthen during secondary forest succession - Hao Ran Lai; Jefferson S. Hall; Benjamin L. Turner; Michiel van Breugel (Ecology, 2017)
Secondary forests are important carbon sinks, but their biomass dynamics vary markedly within and across landscapes. The biotic and abiotic drivers of this variation are still not well understood. We tested the effects of soil resource availability and competition by lianas on the biomass dynamics of young secondary tropical forests in Panama and assessed the extent to which liana effects were mediated by soil resource availability. Over a five‐year period, growth, mortality, and recruitment of woody plants of ≥1 cm diameter were monitored in 84 plots in 3–30‐year‐old secondary forests across the Agua Salud site in central Panama. Biomass dynamics and the effects of lianas and soil resources were examined using (generalized) linear mixed‐effect models and a model averaging approach. There was strong spatial and temporal variation in liana biomass within and across the plots. The relative biomass of lianas had a strong negative effect on overall tree growth, growth of understory trees decreased with soil fertility and dry season soil water content, and the effect of lianas on tree mortality varied with soil fertility. Tree recruitment was not associated with any of the predictor variables. Our model indicates that tree biomass growth across our landscape was reduced with 22% due to competition with lianas, and that the effect of lianas increased during succession, from 19% after five years to 32% after 30 years. The projected liana‐induced growth reduction after 60 years was 47%, which was consistent with data from a nearby site. Our study shows that the observed liana proliferation across tropical forests may reduce the sequestration and storage of carbon in young secondary forests, with important implications for the carbon balance of tropical forest landscapes and consequently for global climate change. Our study highlights the need to incorporate lianas and soil variables in research on the biomass dynamics of secondary forest across tropical landscapes, and the need for well‐replicated longitudinal studies to cover landscape‐level variability in the relevant abiotic and biotic components.

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Evolving Paradigms and Challenges in Estuarine and Coastal Eutrophication Dynamics in a Culturally and Climatically Stressed World - Hans W. Paerl; Nathan S. Hall; Benjamin L. Peierls; Karen L. Rossignol (Estuaries and Coasts, 2014)

Hydrologic Variability and Its Control of Phytoplankton Community Structure and Function in Two Shallow, Coastal, Lagoonal Ecosystems: The Neuse and New River Estuaries, North Carolina, USA - Hans W. Paerl; Nathan S. Hall; Benjamin L. Peierls; Karen L. Rossignol; Alan R. Joyner (Estuaries and Coasts, 2014)

Hypermorphic expression of centromeric retroelement-encoded small RNAs impairs CENP-A loading - Dawn M. Carone; Chu Zhang; Laura E. Hall; Craig Obergfell; Benjamin R. Carone; Michael J. O’Neill; Rachel J. O’Neill (Chromosome Research, 2013)

Non-monotonic Responses of Phytoplankton Biomass Accumulation to Hydrologic Variability: A Comparison of Two Coastal Plain North Carolina Estuaries - Benjamin L. Peierls; Nathan S. Hall; Hans W. Paerl (Estuaries and Coasts, 2012)

Physiological consequences of military high-speed boat transits - Stephen D. Myers; Trevor D. Dobbins; Stuart King; Benjamin Hall; Ruth M. Ayling; Sharon R. Holmes; Tom Gunston; Rosemary Dyson (European Journal of Applied Physiology, 2011)

Phytoplankton Community Indicators of Short- and Long-term Ecological Change in the Anthropogenically and Climatically Impacted Neuse River Estuary, North Carolina, USA - Hans W. Paerl; Karen L. Rossignol; S. Nathan Hall; Benjamin L. Peierls; Michael S. Wetz (Estuaries and Coasts, 2010)

Hydrologic control of nitrogen removal, storage, and export in a mountain stream - Robert Jr. O. Hall; Michelle A. Baker; Christopher D. Arp; Benjamin J. Koch (Limnology and Oceanography, 2009)
Nutrient cycling and export in streams and rivers should vary with flow regime, yet most studies of stream nutrient transformation do not include hydrologic variability. We used a stable isotope tracer of nitrogen ( 15 N) to measure nitrate (NO 3 − ) uptake, storage, and export in a mountain stream, Spring Creek, Idaho, U.S.A. We conducted two tracer tests of 2‐week duration during snowmelt and baseflow. Dissolved and particulate forms of 15 N were monitored over three seasons to test the hypothesis that stream N cycling would be dominated by export during floods, and storage during low flow. Floods exported more N than during baseflow conditions; however, snowmelt floods had higher than expected demand for NO 3 − because of hyporheic exchange. residence times of benthic N during both tracer tests were longer than 100 d for ephemeral pools such as benthic algae and wood biofilms. Residence times were much longer in fine detritus, insects, and the particulate N from the hyporheic zone, showing that assimilation and hydrologic storage can be important mechanisms for retaining particulate N. Of the tracer N stored in the stream, the primary form of export was via seston during periods of high flows, produced by summer rainstorms or spring snowmelt the following year. Spring Creek is not necessarily a conduit for nutrients during high flow; hydrologic exchange between the stream and its valley represents an important storage mechanism.

A phylogeographical analysis of the range disjunction for foxtail pine ( Pinus balfouriana , Pinaceae): the role of Pleistocene glaciation - ANDREW J. ECKERT; BRANDON R. TEARSE; BENJAMIN D. HALL (Molecular Ecology, 2008)
Biogeographical patterns within the California Floristic Province have been greatly affected by geological and climatic events. Here, we investigate the phylogeography of foxtail pine ( Pinus balfouriana ) in an effort to date its range disjunction using molecular data and to further our understanding of phylogeographical patterns for plants within the California Floristic Province. The distribution of foxtail pine is characterized by a 500‐km disjunction separating populations located in the Klamath Mountains from those in the southern Sierra Nevada. Previous authors suggested that this disjunction occurred approximately 4000–8000 years ago during the Holocene Xerotherm when western North America became warmer and drier. Those dates, however, are inconsistent with the morphological differences that separate regional populations into formally recognized subspecies. Using the coalescent‐based isolation with migration model and DNA sequence data from the chloroplast, mitochondrial, and nuclear genomes, we evaluate several hypotheses addressing the timing of this range disjunction and its effects on subsequent patterns of gene flow. Results from all three genomes are largely consistent with Middle to Early Pleistocene divergence dates. Those dates correspond to the Sherwin glaciation, which was the largest Pleistocene glacial episode in the Sierra Nevada. Gene flow, moreover, was only documented using data from the chloroplast genome, suggesting that low levels of long‐distance pollen dispersal ( N e m

A Multistep Process Gave Rise to RNA Polymerase IV of Land Plants - Jie Luo; Benjamin D. Hall (Journal of Molecular Evolution, 2007)

Are Red Algae Plants? A Critical Evaluation of Three Key Molecular Data Sets - John W. Stiller; Jennifer Riley; Benjamin D. Hall (Journal of Molecular Evolution, 2001)